Pretreatment method of forchlorfenuron residues in loquat by HPLC analysis - YANG Chunping; LI Zhaojun; NING Hong; CHEN Huabao; GONG Guoshu; YANG Jizhi; ZHANG Min (浙江大学学报. 农业与生命科学版, 2016)
Forchlorfenuron,1-(2-chloro-4-pyridyl)-3-phenyl, is a multipurpose plant growth regulator. The previous reports showed that forchlorfenuron was a relatively safe and low-toxic pesticide without teratogenic and mutagenic effects on human and animals. However, recent researches showed that excessive exposure of forchlorfenuron could cause the disorder of protein metabolism, mild emphysema. Therefore, residue detection of forchlorfenuron in fruits and vegetables is imperative.High-performance liquid chromatography (HPLC) analysis is a common detection method. The suitable conditions for the extraction and purification of sample play an important role prior to HPLC analysis.In this study, the extraction efficiency of forchlorfenuron residues in loquat was compared using matrix dispersive solid phase extraction and QuEChERS (quick, easy, cheap, effective, rugged, safe).The results showed that QuEChERS was a more suitable pretreatment method for the determination of forchlorfenuron residues in loquat, because it had obviously higher average recoveries than the matrix dispersive solid phase extraction. Effects of different extraction and purification conditions on QuEChERS were further studied. The optimal conditions obtained were that 8.0 g of loquat samples were extracted with 16 mL of acetonitrile for 20 min, and then salted out for dehydration by m (anhydrous magnesium sulfate)∶m (sodium chloride)=3∶2, and ultimately purified by m (primary secondary amine (PSA))∶m (C18)=1∶1 for 3 min. The forchlorfenuron residues in loquat could be completely separated from impurities under these optimal conditions, and furthermore, the spiked recoveries of forchlorfenuron in loquat were 80%-100%, with coefficient of variation (CV) in the range of 3.1%-4.8%.It was concluded that our method of pretreatment could effectively extract and purify forchlorfenuron residues in loquat.